Fake news in context - Farmer, Lesley S. J. (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Fake News in Context defines fake news and sets it within a historical and international context. Helping readers to become more skilled at detecting misinformation, the book also demonstrates how such knowledge can be leveraged to facilitate more effective engagement in civic education. Distinguishing between fake news and other forms of misinformation, the book explains the complete communication cycle of fake news: how and why it is created, disseminated, and accessed. The book then explains the physical and psychological reasons why people believe fake news. Providing generic methods for identifying fake news, Farmer also explains the use of fact-checking tools and automated algorithms. The book then details how various literacies, including news, media, visual, information, digital and data, offer unique concepts and skills that can help interpret fake news. Arguing that individuals and groups can respond and counter fake news, which leads to civic engagement and digital citizenship, the book concludes by providing strategies for instruction and tips for collaborating with librarians. Including a range of international examples, Fake News in Context will be of interest to teaching faculty, and students of library and information science, communication studies, media studies, politics and journalism. Librarians and information professionals will also find a valuable resource in this book"--
OCLC-licensed vendor bibliographic record.
Keywords: Fake news; Media literacy; SOCIAL SCIENCE / Media Studies